Analysis of students' metacognition in solving mathematics problems. (August 2020) - Imaya, I A; Budiyono,; Nurhasanah, F
Abstract: Metacognition is a thought about the awareness of thinking itself to plan, organize strategy information, monitor strategies, debugging strategies and assess the results of their abilities. Student activities in the use of their awareness can be used to solve problems. Mathematical problems solving is an important thing in the process of learning mathematics so that complex ways of thinking are needed. This study aims to analyze the level of metacognition of students in Boyolali district in solving problems based on differences in mathematical scores and gender. This study is a qualitative study using written test data and interviews with students and mathematics teachers. The results showed that the level of metacognition of male students who had high mathematical scores was at the level of aware use, the subjects are aware of what they are doing and can be used to solve problems, but the subject cannot solve it well and cannot correct his mistakes. The level of metacognition of female students who have high, medium and low math scores are at the level of tracit use. The student cannot understand the problem at hand and does not know the concept used.